Continuing professional development (CPD) in ELT: Lessons from Argentina - Pérez Berbain, Mercedes; Polastri, Vanesa; Leirós, Analía (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2023)
This research article reports on a study of the lived experiences of 14 English language teachers who engaged in an inclusive, online CPD activity: 11 participating teachers, the tutor, and the organisers from an Argentinian ELT teachers’ association. Based on a qualitative research design, this study explores the participants' growth and understanding of CPD, where the latter is considered the metadimension of the former. Data were gathered through in-depth, oral, individual interviews. Drawing on thematic analysis, the researchers found that participants enhanced their teaching approach, developed teaching competencies, and challenged their previous views on teacher CPD. Specifically, participants were able to conceptualise an effective CPD activity as active, context-driven, inclusive, interactive, collaborative, reflective, self-directed, appealing, goal-oriented, well-structured, emotionally-satisfying, as well as one that fosters socially-constructed knowledge and is constantly updated with the participants’ ideas. The study argues that effective CPD regards teachers’ renewed ideas as enactment of decentred ELT pedagogies.